Uma análise da produção acadêmica sobre os usos da pesquisa-ação em processos de inclusão escolar : entre o agir comunicativo e o agir estratégico - Almeida, Mariangela Lima de (2010)
This study investigates the theoretical-methodological and epistemological presuppositions of the action research used in academic production in the field of Special Education/school inclusion. It analyzes the theses and dissertations defended all over the country in the period between 1999 and March 2008. It maps 45 studies that constitute the analysis corpus. This study is developed from the idea of research on research , using epistemological analysis as a trigger for discussions about the implicit and explicit aspects in the dialectics between question and response in the studies analyzed. The scheme chart inspired on the principles of paradigmatic scheme was used as an instrument to organize the texts. From a theoretical-methodological perspective, the study is based on the Theory of Communicative Action created by Jürgen Habermas in order to understand and analyze the presuppositions and knowledge of the action research assumed in the study, as well as the way they are approached by the authors. It builds dialogues based on argumentation between authors and researchers so as to achieve agreement and understanding. It observes that the methodological approach of the action research is incorporated into a significant number of studies from the perspective of school inclusion that mainly problematizes the continuing education of teachers and the teaching practice. It makes the theoretical-methodological arguments for the action research emerge from the dialogue between the authors and researchers: the relationship between authors (researchers) and actors (context participants); the roles attributed to these subjects; the constitution of the research question; the action research dynamics; and the dialectics between the understanding and transformation of reality. Through discussions among the authors, the study reveals that these presuppositions are used in different ways during the investigation, because of the different ways in which these authors conceive action in the action research process. It shows that, when the actions are carried out through communicative acting, there is a search for mutual understanding that can evolve into normative agreements by means of shared intersubjectivity. In this case, the action research process is carried out through critical and collaborative self-reflection. From a different perspective, when the actions are guided by the strategic acting, they are carried out based on individual interests materialized at intervention levels which focus on predefined results. The study verifies that, from the first perspective, the occurring changes begin as a process and tend to transcend immediacy, achieving the socio-political sphere. From the second perspective, the changes tend to be immediate and pragmatic. It is possible to consider that, in the Special Education field and from the school inclusion perspective, action research contributes mainly to a feasible collaborative and collective work in the school context. As far as future analyses are concerned, the study shows the importance of constructing knowledge based on reflections and actions with the other so as to understand the path of the research process